The anti-proliferative and anti-androgenic activity of different pomegranate accessions. (October 2016) - Orgil, Ola; Spector, Limor; Holland, Doron; Mahajna, Jamal; Amir, Rachel
Highlights: Twenty-nine accessions were studied for their in vitro ability to inhibit cancer cell lines. Different accessions exhibit different anti-proliferative activities against the cell lines. Peels have significantly higher anti-proliferative activity than aril juice and seeds. Peels have compounds that reduced androgen receptor function. Abstract: This study monitored the anti-proliferative activity of pomegranate ( Punica granatum L.) peel homogenates against breast (MCF7 and MDA-MB-453) and prostate (LNCaP and PC-3) cancer cell lines using 29 different accessions to study the natural diversity in these accessions. Using MTT method, it was revealed that high anti-proliferative activity was observed against MCF7, MDA-MB-453 and LNCaP (androgen-dependent) cell lines for most accessions, while the androgen-independent prostate cancer cell line, PC-3, exhibited relatively high resistance. Peel extracts displayed the highest LNCaP inhibition activity compared to aril juice and seed homogenates. Eight accessions exhibiting the highest anti-proliferative activity were studied further using the LNCaP and PC-3 cancer cells. IC50 and clonogenicity inhibition were determined. Several accessions were found to inhibit androgen receptor activity but not NF-κB transcription function. This study illustrated the importance of exploiting natural pomegranate variation to identify accessions exhibiting potential selective activity for the treatment of specific types of cancer.